Environmental Literacy of ISCED 2 Pupils in Poland - Svobodová, Silvie (Revija za elementarno izobraževanje, 2023)
Environmental literacy represents the extent of environmental knowledge, attitudes, sensitivity and responsible environmental behaviour. The presented study focuses on the environmental literacy of ISCED 2 pupils in Poland. The survey analysed the relationship between the environmental literacy and its significant determinants. The connection between environmental literacy and gender, school grade and leisure time of the respondents was determined. More than three hundred respondents took part in the testing.A moderate positive relationship between the dimensions of environmental literacy was demonstrated. Analyses have also shown that environmental literacy is significantly determined by gender, school grade and leisure activities, especially outdoor activities.